CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface as well as preparation method and application of CuS / C composite positive electrode material

By using CuS/C composite cathode material rich in carbon-sulfur heterointerface in magnesium batteries, the problems of low capacity, poor stability and low Coulomb efficiency of copper sulfide cathode are solved, and higher cycle stability and efficiency are achieved.

CN119581513AActive Publication Date: 2025-03-07WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411631481.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-07
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The copper sulfide positive electrode in existing magnesium batteries has low capacity, poor stability and low Coulomb efficiency, which is mainly due to poor phase change reversibility and excessive copper ion dissolution during CuS cycle.

Method used

Using CuS/C composite positive electrode material rich in carbon-sulfur heterointerface, a heterointerface containing carbon-sulfur bond is formed by distributing CuS nanoparticles on the surface of the carbon substrate material and forming a heterointerface containing carbon-sulfur bonds at the interface between the CuS nanoparticles and the carbon substrate, the activation energy of sulfur atoms in the Cu-S tetrahedron is reduced, and the reversible phase transition between Cu2S and CuS is promoted.

Benefits of technology

It effectively improves the cyclic stability and Coulomb efficiency of CuS positive electrode, reduces the shuttle effect of copper ions, and enhances the cyclic performance and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581513A_ABST
    Figure CN119581513A_ABST
Patent Text Reader

Abstract

According to the CuS / C composite positive electrode material rich in the carbon-sulfur heterogeneous interface and the preparation method of the CuS / C composite positive electrode material rich in the carbon-sulfur heterogeneous interface, the rich carbon-sulfur (C-S) heterogeneous interface is successfully constructed by anchoring CuS nanoparticles on a carbon substrate material. The carbon-sulfur bond outside the plane effectively activates the Cu-S tetrahedral structure, and reduces the formation energy barrier of the disulfide bond (S-S) in CuS, thereby significantly improving the reversible phase change ability of Cu2S and CuS in the charge-discharge process. According to the composite positive electrode material provided by the invention, the problem of copper ion dissolution caused by volume expansion is effectively relieved, so that the cycling stability and electrochemical performance of the material are remarkably improved, efficient transmission of magnesium ions is realized, and a new direction is provided for developing a conversion type positive electrode material with rapid ion kinetics and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials and electrochemical technology, and specifically relates to a CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) are one of the most advanced energy storage technologies and are widely used in electric vehicles and portable electronic devices. However, the scarcity of lithium resources in the earth's crust (only 0.0022 wt%) and their uneven distribution limit their sustainable development. Therefore, the development of new battery systems has become particularly important. Magnesium (Mg) is an element with abundant resources and a small ionic radius (0.72 Å). Magnesium batteries not only have higher energy density than LIBs, but also do not form dendrites during the cycle, thus having higher safety. However, divalent Mg 2+ The strong electrostatic interaction with the host material leads to slow diffusion kinetics during the insertion / deinsertion process, thus affecting the cycling stability. Therefore, it is necessary to find suitable cathode materials to achieve efficient and stable Mg 2+ Storage has become the focus of current research.

[0003] In terms of magnesium ion storage, inorganic cathode materials are mainly divided into two categories: intercalation type and conversion type. Intercalation type cathode materials (such as V2O5, MoO3) are widely studied due to their higher operating voltage and smaller voltage hysteresis, but their capacity is relatively limited. In contrast, conversion type cathode materials utilize the multivalent state of elements and are not restricted by a fixed lattice structure, showing a higher theoretical capacity. CuS, as a typical conversion material, has a capacity of about 560 mAhg -1 CuS has attracted much attention due to its high theoretical capacity and low cost. However, the poor reversibility of phase transition during cycling limits its application. By comparing the crystal structures of Cu2S and CuS, we speculate that the formation of SS bonds is the key step in the phase transition.

[0004] In summary, reducing the formation energy of SS bonds promotes the conversion of Cu2S to CuS, while reducing the dissolution of copper ions and achieving Mg 2+ The rapid diffusion of magnesium batteries, thereby improving the coulombic efficiency and cycle stability, is a problem that needs to be solved urgently. Summary of the invention

[0005] Conversion cathodes have become promising cathode materials in rechargeable magnesium batteries (RMBs) due to their multivalent state transitions and high energy density. However, their development is severely restricted by the poor reversibility of phase transitions and the shuttling phenomenon of active materials. Therefore, the present invention proposes a CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface and a preparation method thereof to solve the problems of low capacity, poor stability and low coulombic efficiency of copper sulfide cathodes in existing magnesium batteries. The CS bond at the CuS cathode interface can activate the stable Cu-S tetrahedral structure and reduce the formation energy of disulfide bonds (SS) in CuS, promoting the reversible phase transition from Cu2S to copper sulfide.

[0006] To achieve the above-mentioned object, the present invention provides a CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface, characterized in that the composite positive electrode material comprises a carbon base material, and CuS nanoparticles distributed on the surface of the carbon base material, the CuS nanoparticles are in close contact with the carbon base, and a heterogeneous interface containing carbon-sulfur bonds is formed at the interface where the CuS nanoparticles contact the carbon base. Furthermore, the carbon substrate material is one or more of graphene, Ketjen black, porous carbon, acetylene black, carbon nanotubes, and carbon fibers, preferably graphene.

[0007] Furthermore, in the composite positive electrode material, the mass fraction of the carbon base material is 10%~30%.

[0008] Furthermore, the CuS nanoparticles have a hexagonal phase.

[0009] A method for preparing a CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface is also provided, comprising the following steps: S1, adding copper salt and tris(hydroxymethyl)aminomethane to a solution containing a carbon substrate material respectively, and stirring thoroughly to obtain a mixed solution A; S2, adding aqueous ammonia to the mixed solution A, and stirring thoroughly to obtain a mixed solution B; S3, adding NaOH solution to mixed solution B, and stirring thoroughly to obtain mixed solution C; S4, adding thiourea to the mixed solution C, and stirring thoroughly to obtain a mixed solution D; S5, after the mixed solution D is allowed to stand, the supernatant is poured out, and the hydrazine hydrate solution is added to the mixed solution D, and the mixed solution E is obtained after sufficient stirring; S6. The mixed solution E is heated in a water bath, and then the precipitate is washed alternately with deionized water and ethanol for multiple times, and vacuum dried to obtain a CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface.

[0010] Furthermore, the copper salt is one or more of copper chloride, sulfate, nitrate and acetate.

[0011] Furthermore, in step S1, the molar ratio of copper salt to tris(hydroxymethyl)aminomethane is 1:1-5; preferably, the molar ratio is 1:1-3; and the concentration of the carbon-based material is 1 mg / mL.

[0012] Furthermore, in step S2, the volume of the ammonia solution added is 5 mL-20 mL, and the concentration of the ammonia solution is 2 M; in step S3, the volume of the NaOH solution added is 5 mL-20 mL, and the concentration of the NaOH solution is 1 M; in step S4, the volume of the thiourea solution added is 1 mL to 10 mL, and the thiourea solution is 1 M.

[0013] Furthermore, in step S5, the standing time is 1 h-5 h; the volume of the hydrazine hydrate solution added is 1 mL-20 mL, and the mass fraction of hydrazine hydrate in the hydrazine hydrate solution is 80%; in step S6, the water bath heating temperature is 50 ℃-80 ℃, and the time is 2 h-4 h; the temperature of the vacuum drying treatment is 50 ℃-80 ℃, and the time is 4 h-12 h.

[0014] Also provided is a use of the nanocomposite material prepared by the above-mentioned method in a magnesium ion battery.

[0015] The beneficial effects of the present invention are: (1) In the customized copper sulfide cathode material structure rich in carbon-sulfur (CS) heterogeneous interface, the carbon-sulfur (CS) bond at the interface effectively reduces the activation energy of sulfur atoms in the Cu-S tetrahedron, reduces the formation energy of SS bonds, and promotes the conversion between Cu2S and CuS during the charge and discharge process.

[0016] (2) By achieving a more reversible phase transition, the composite material of the present invention effectively alleviates the volume expansion of the CuS positive electrode during the cycle and inhibits the shuttling effect of copper ions, thereby improving the cycle stability and efficiency of the battery.

[0017] (3) The present invention provides a feasible strategy for promoting reversible phase transition and inhibiting the shuttle effect of conversion-type positive electrode active materials for the development of high-energy multivalent ion batteries. In addition, the preparation method of the present invention is simple, the raw materials are cheap and readily available, suitable for large-scale production, and has the potential for market promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a SEM image of the CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface described in Example 1 of the present invention; Figure 2 TEM, HRTEM and SAED images of the CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface described in Example 1 of the present invention; Figure 3 This is a Raman comparison diagram of the CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface and copper sulfide according to Example 1 of the present invention; Figure 4 This is a cyclic voltammetry comparison diagram of the CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface and the copper sulfide positive electrode described in Example 1 of the present invention; Figure 5 A comparison chart of the cycle performance of the CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface and the copper sulfide positive electrode described in Example 1 of the present invention; Figure 6 A comparison chart of the rate performance of the CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface and the copper sulfide positive electrode described in Example 1 of the present invention. DETAILED DESCRIPTION

[0019] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.

[0020] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0021] Example 1 This embodiment provides a method for preparing a CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface, comprising the following steps: S1. Adding CuCl2·H2O powder and tris(hydroxymethyl)aminomethane powder into the graphene oxide solution and stirring thoroughly to obtain a mixed solution A; S2, adding aqueous ammonia to the mixed solution A, and stirring thoroughly to obtain a mixed solution B; S3, adding NaOH solution to mixed solution B, and stirring thoroughly to obtain mixed solution C; S4, the thiourea was added to the mixed solution C, and stirred thoroughly to obtain a mixed solution D; S5, the mixed solution D was allowed to stand, the supernatant was poured out, and then the hydrazine hydrate solution was added to the mixed solution D, and stirred thoroughly to obtain a mixed solution E; S6. After heating the mixed solution E in a water bath, the precipitate is washed alternately with deionized water and ethanol for multiple times, and vacuum dried to obtain a copper sulfide positive electrode material rich in carbon-sulfur (CS) heterogeneous interface.

[0022] 1) At room temperature, take 60 ml of graphene oxide (1 mg / ml) and place it in a beaker. Then weigh 0.85 g of CuCl2·H2O powder and 1.75 g of tris(hydroxymethyl)aminomethane powder and pour them into the beaker. After magnetic stirring for ten minutes, a uniform mixed solution A is obtained. 2) Pour 10 ml of ammonia solution into mixed solution A and stir magnetically for ten minutes to obtain a uniform mixed solution B; 3) Pour 6 ml of thiourea solution into mixed solution B and stir magnetically for ten minutes to obtain a uniform mixed solution C; 4) Weigh 10 ml of NaOH solution and pour it into mixed solution C. Stir magnetically for ten minutes to obtain a uniform mixed solution D. 5) After the mixed solution D was allowed to stand for 3 h, the supernatant was poured out, and 5 ml of hydrazine hydrate solution was diluted to 50 ml with deionized water, and added to the mixed solution D. After sufficient stirring, a uniform mixed solution E was obtained; 6) The mixed solution E was heated in a water bath for 3 h, and then the precipitate was washed alternately with deionized water and ethanol for multiple times, and dried in a vacuum drying oven at 60 °C for 6 h to obtain a CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface. The performance test of the CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface prepared in Example 1 was carried out. The results are as follows: Figure 1-3 shown.

[0023] Figure 1 This is a scanning electron microscope (SEM) image of a CuS / C composite cathode material rich in carbon-sulfur heterogeneous interfaces. It can be seen from the figure that the CuS nanoparticles are evenly dispersed on the graphene substrate and are in close contact with the graphene, forming a large number of carbon-sulfur (CS) heterogeneous interfaces.

[0024] Figure 2The transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED) images of CuS nanoparticles. The TEM image reveals that the CuS nanoparticles are partially dispersed and encapsulated on the surface of the graphene sheet, verifying the observation results of SEM. Analysis of the HRTEM image shows that two different lattice fringes are identified in the composite structure of CuS and graphene. The clear lattice spacing is 3.23 Å, which belongs to the (101) crystal plane of the hexagonal phase CuS, while the fuzzy green area indicates the amorphous graphene structure. In addition, the lattice fringes gradually transition to the amorphous phase without obvious domain boundaries, indicating that there is an interaction between CuS nanoparticles and graphene. The SAED image further confirms this interaction, showing diffraction points corresponding to the (110) and (102) crystal planes of polycrystalline CuS and the (002) crystal plane of graphene.

[0025] Figure 3 The Raman spectra of CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface and pure CuS are compared. As can be seen from the figure, the Raman spectrum of pure CuS has a significant peak at 455 cm⁻¹, corresponding to the SS bond vibration mode in the crystal structure. In contrast, the Raman spectrum of the CuS@G composite material shows the characteristic peaks of graphene, at 1349 cm -1 (D band) and 1595 cm -1 (G band). In addition, 601 cm -1 and 1054 cm -1 The new peak at is attributed to the vibration mode of the C-S bond, indicating the existence of abundant C-S heterointerfaces between CuS and graphene.

[0026] The CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface prepared in Example 1 was directly used as the positive electrode, the magnesium sheet was used as the negative electrode, Mg(MPFB)2 was used as the electrolyte, and GF / D glass fiber was used as the separator to assemble a CR2016 type button-type full battery. The button-type full battery was tested, and the results were as follows Figure 4-6 shown.

[0027] Figure 4The cyclic voltammetry (CV) comparison diagram of CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface and pure CuS cathode. The comparison shows that the introduction of graphene significantly affects the morphology of the CV curve. In the first three cycles, the reduction peak intensity of the pure CuS cathode decreased successively, while the peak intensity of the copper sulfide cathode rich in carbon-sulfur (CS) heterogeneous interface remained relatively stable. After the first 10 cycles, the CV curve of the pure CuS cathode showed two obvious reduction peaks at 1.75 V and 1.90 V. In contrast, the copper sulfide cathode rich in carbon-sulfur (CS) heterogeneous interface showed three clear reduction peaks at 1.54 V, 1.80 V and 1.90 V in the third cycle, indicating a more reversible phase transition process during charging.

[0028] Figure 5 The cycling performance comparison of the CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface and the pure CuS cathode. The specific capacity of the pure CuS cathode decays rapidly, while the copper sulfide cathode rich in carbon-sulfur heterogeneous interface decays rapidly at 100 mA g -1 After 100 cycles at the same current density, the battery exhibited a stable specific capacity of 212 mAh g -1 , and maintained 83.2% of its initial capacity.

[0029] Figure 6 The figure shows the rate performance comparison between the CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface and the pure CuS cathode. The copper sulfide cathode rich in carbon-sulfur heterogeneous interface has achieved a significant improvement in rate performance. -1 At a current density of more than 280 mAh g -1 Even if the current density is increased to 1 A g -1 The copper sulfide cathode rich in carbon-sulfur heterogeneous interface still maintains 160.5 mAh g -1 The specific capacity is equivalent to 57.3% of the initial specific capacity, showing excellent rate performance.

[0030] The above test results show that the CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface has excellent electrochemical properties and can be used in highly reversible magnesium batteries.

[0031] Example 2 The difference between this embodiment and embodiment 1 is that: At room temperature, 60 ml of graphene oxide (0.5 mg / ml) was placed in a beaker, and 0.85 g of CuCl2·H2O powder and 1.75 g of tris(hydroxymethyl)aminomethane powder were weighed and poured into the beaker. After magnetic stirring for ten minutes, a uniform mixed solution A was obtained. The remaining steps and parameters are the same as those in Example 1.

[0032] The CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface obtained in Example 2 was used as the positive electrode combination electrode, and a button-type full battery was assembled and tested according to the above method. The test results showed that at 0.1 A g -1 The discharge capacity of the electrode is 197 mAh g -1 , the capacity retention rate is only 68%. Analysis shows that when the graphene content is low (10%), the electrochemical performance of the material is poor. Further analysis and speculation indicate that when the graphene content is low (10%), fewer CS bonds are formed between copper sulfide nanoparticles and graphene, which limits the promotion of the reversible phase transformation of copper sulfide, resulting in poor performance.

[0033] Example 3 The difference between this embodiment and embodiment 1 is that: At room temperature, 60 ml of graphene oxide (1.5 mg / ml) was placed in a beaker, and 0.85 g of CuCl2·H2O powder and 1.75 g of tris(hydroxymethyl)aminomethane powder were weighed and poured into the beaker. After magnetic stirring for ten minutes, a uniform mixed solution A was obtained. The remaining steps and parameters are the same as those in Example 1.

[0034] The CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface obtained in Example 3 was used as the positive electrode combination electrode, and a button-type full battery was assembled and tested according to the above method. The test results showed that at 0.1 A g -1 At the current density, the discharge capacity of the electrode is 228 mAh g -1 , the capacity retention rate is only 80%. Analysis shows that when the graphene content is high (30%), the electrochemical performance of the material decreases. Further analysis and speculation indicate that when the graphene content is high (30%), copper sulfide only forms CS bonds with graphene at the interface, while the graphene farther away cannot participate, cannot promote the reversible phase transition, and has limited contribution to capacity, resulting in performance degradation.

[0035] Example 4 The difference between this embodiment and embodiment 1 is that: At room temperature, 60 g of Ketjen black (1 mg / ml) was placed in a beaker, and 0.85 g of CuCl2·H2O powder and 1.75 g of tris(hydroxymethyl)aminomethane powder were weighed and poured into the beaker. After magnetic stirring for ten minutes, a uniform mixed solution A was obtained. The remaining steps and parameters are the same as those in Example 1.

[0036] The copper sulfide material rich in carbon-sulfur heterogeneous interface obtained in Example 4 was used as the positive electrode combination electrode, and a button-type full battery was assembled and tested according to the above method. The test results showed that at 0.1 A g -1 At the current density, the discharge capacity of the electrode is 201 mAh g -1 , the capacity retention rate is only 76%. Analysis shows that the two-dimensional structure of graphene (rGO) can anchor more CuS nanoparticles, and CuS nanoparticles can be better dispersed on the surface of carbon materials, successfully constructing a rich carbon-sulfur (CS) heterogeneous interface. Ordinary carbon materials cannot fully anchor CuS nanoparticles. Therefore, the content of carbon-sulfur (CS) heterogeneous interface that can be formed in the overall material is relatively small, which limits the promotion of the reversible phase transformation of copper sulfide, and has limited contribution to capacity, resulting in performance degradation.

[0037] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface, characterized in that: The composite positive electrode material comprises a carbon substrate material and CuS nanoparticles distributed on the surface of the carbon substrate material. The CuS nanoparticles are in close contact with the carbon substrate, and a heterogeneous interface containing carbon-sulfur bonds is formed at the interface where the CuS nanoparticles and the carbon substrate contact each other.

2. The CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface according to claim 1, characterized in that: The carbon substrate material is one or more of graphene, Ketjen black, porous carbon, acetylene black, carbon nanotubes, and carbon fibers, preferably graphene.

3. The CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface according to claim 1, characterized in that: In the composite positive electrode material, the mass fraction of the carbon base material is 10% to 30%.

4. The CuS / C composite cathode material rich in carbon-sulfur heterogeneous interface according to claim 1, characterized in that: The CuS nanoparticles have a hexagonal phase.

5. A method for preparing a CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface according to any one of claims 1 to 4, characterized in that: The steps include: S1, adding copper salt and tris(hydroxymethyl)aminomethane to a solution containing a carbon substrate material respectively, and stirring thoroughly to obtain a mixed solution A; S2, adding aqueous ammonia to the mixed solution A, and stirring thoroughly to obtain a mixed solution B; S3, adding NaOH solution to mixed solution B, and stirring thoroughly to obtain mixed solution C; S4, adding thiourea to the mixed solution C, and stirring thoroughly to obtain a mixed solution D; S5, after the mixed solution D is allowed to stand, the supernatant is poured out, and the hydrazine hydrate solution is added to the mixed solution D, and the mixed solution E is obtained after sufficient stirring; S6. The mixed solution E is heated in a water bath, and then the precipitate is washed alternately with deionized water and ethanol for multiple times, and vacuum dried to obtain a CuS / C composite positive electrode material rich in carbon-sulfur heterogeneous interface.

6. The preparation method according to claim 5, characterized in that: The copper salt is one or more of copper chloride, sulfate, nitrate and acetate.

7. The preparation method according to claim 5, characterized in that: In step S1, the molar ratio of copper salt to tris(hydroxymethyl)aminomethane is 1:1-5; preferably, the molar ratio is 1:1-3.

8. The preparation method according to claim 5, characterized in that In step S2, the volume of the ammonia solution added is 5 mL-20 mL; in step S3, the volume of the NaOH solution added is 5 mL-20 mL; in step S4, the volume of the thiourea solution added is 1 mL to 10 mL.

9. The preparation method according to claim 5, characterized in that In step S5, the standing time is 1 h-5 h; the volume of the hydrazine hydrate solution added is 1 mL-20 mL; in step S6, the water bath heating temperature is 50 ° C-80 ° C, and the time is 2 h-4 h; the temperature of the vacuum drying treatment is 50 ° C-80 ° C, and the time is 4 h-12 h.

10. Use of the nanocomposite material according to claims 1 to 4 or the nanocomposite material prepared by the method according to claims 5 to 9 in magnesium ion batteries.

Citation Information

Patent Citations

  • Mn doped CuS hollow porous graded nanosphere electrode material and preparation method and application thereof

    CN107275627A

  • Sandwich structure composite material for positive electrode of magnesium ion battery and preparation method of sandwich structure composite material

    CN114156447A